Many pretty toys - Adams, Hazard, 1926-2023 (SUNY series in postmodern culture., 1999)
A Vietnam War sit-in at a West Coast university ends in tragedy when a bomb explodes, killing one of the students. A look at the way the war politicized college life. By the author of The Academic Tribes. -- Provided by publisher.